Is prednisone still a reasonable option in the treatment of withdrawal headache in patients with chronic migraine and medication overuse headache in the age of CGRP antibodies? A narrative review. Issue 10 (27th November 2022) - Kaltseis, Katharina; Hamann, Till; Gaul, Charly; Broessner, Gregor
Abstract: Objective: Along with the development of novel migraine therapies as the monoclonal antibodies against calcitonin gene‐related peptide (CGRP) and its receptor, the question arises if the treatment of chronic migraine (CM) and medication overuse headache (MOH) must be reconsidered. Have previous therapeutic approaches, including glucocorticoids, lost their role in the management of this debilitating disorder? In this narrative review, we present an overview of the available treatment options in CM and MOH in light of CGRP antibodies as well as an evaluation of the role of glucocorticoids in withdrawal therapy. Background: Chronic migraine and medication overuse continues to be a difficult to treat condition. To date, potent treatment options are scarce and algorithms for advising patients with MOH are often still based on expert consensus rather than evidence‐based medicine. For years and probably due to lack of effective alternatives, glucocorticoids have been used in MOH, especially to alleviate withdrawal symptoms caused by detoxification. Small case series report positive effects of steroids in this respective patient group; however, randomized controlled trials did not show a consistent benefit, although this may be due to methodological limitations. Because of these discrepancies, their role in MOH has been under debate ever since. Methods: We searched the electronic database PubMed for articles up to June 1, 2022 on the use of glucocorticoids in CM and MOH. Conclusion: Despite popular use in clinical practice, there is currently still no scientific evidence for the efficacy of glucocorticoids in patients with CM and MOH. Treatment with monoclonal antibodies achieved high transition rates from medication overuse to non‐overuse. However, further research is needed to evaluate the additional benefit of these new agents.